The Rise of Artificial Intelligence in Pharmacy: Transforming Medication Management and Patient Care - Anastasya, Gracia; Khairinisa, Miski A. (Pharmacology and Clinical Pharmacy Research, 2024)
Artificial intelligence (AI) is rapidly transforming healthcare, with significant implications for pharmacy practice. This review explores the diverse applications of AI in pharmacy, emphasizing its potential to revolutionize medication management, patient care, public health, disease management, and pharmacy workflow efficiency. AI algorithms can analyze a vast amount of patient data, allowing pharmacists to identify potential drug interactions, evaluate medication safety and effectiveness, and offer personalized treatment suggestions. In the realm of public health, AI supports disease management through epidemiological monitoring and targeted interventions. Additionally, AI-driven robotic dispensing systems and automated inventory management enhance pharmacy workflow efficiency by streamlining operations and optimizing resource allocation. Telepharmacy, further augmented by AI, expands access to healthcare, promotes patient engagement, and facilitates remote clinical consultations, thereby improving overall care delivery. Despite these advancements, challenges such as data privacy and potential bias in AI algorithms persist. However, the potential of AI in pharmacy is undeniable. By addressing these challenges and fostering collaboration among pharmacists, AI developers, and regulatory bodies, the future of pharmacy is poised to deliver personalized care, improved patient outcomes, and enhanced public health.This integration of AI into pharmacy practice represents a significant step toward a more effective and patient-centered approach to healthcare.